Additional file 2 of Peripheral myeloid-derived suppressor cells are good biomarkers of the efficacy of fingolimod in multiple sclerosis - Celia Camacho-Toledano; Isabel Machín-Díaz; Leticia Calahorra; María Cabañas-Cotillas; David Otaegui; Tamara Castillo-Triviño; Luisa María Villar; Lucienne Costa-Frossard; Manuel Comabella; Luciana Midaglia; José Manuel García-Domínguez; Jennifer García-Arocha; et al. (figshare, 2022)
Additional file 2: Table S2. Demographic data from the fingolimod patients included in the study.
Keywords: Biochemistry; Medicine; Cell Biology; Neuroscience; Pharmacology; Ecology; Immunology; Cancer; 110309 Infectious Diseases; 60506 Virology